STRATEGI PENGEMBANGAN PENGOLAHAN KOPI ARABIKA SEBAGAI DAYA TARIK WISATA GASTRONOMI DI DESA CATUR, KINTAMANI, BALI - I Made Hendrayana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Catur Village is a center for Kintamani Arabica Coffee production, the distribution of the coffee products has been carried out throughout Bali to foreign countries such as Japan, Europe, America, and Australia with the brand